The Effect of Intradialytic Exercise on Reducing Fatigue Levels in Chronic Kidney Failure Patients Undergoing Hemodialysis at Prof. Dr. H. Aloei Saboe Hospital - Dedi A. Husain; Ita Sulistiani; Indra (Universitas Muhammadiyah Palu, 2026)
Chronic Kidney Failure is a health problem that requires patients to undergo long-term therapy, namely hemodialysis. Fatigue is the main complaint of hemodialysis patients that is subjective, affects the quality of life, and often has not been handled optimally in the Hemodialysis Unit of Prof. Dr. H. Aloei Saboe Hospital. Therefore, intradialytic exercise in the form of light physical exercise as a non-pharmacological intervention is believed to be able to overcome the fatigue problem . This study aims to analyze the effect of intradialytic exercise on reducing fatigue levels in chronic kidney failure patients undergoing hemodialysis at Prof. Dr. H. Aloei Saboe Hospital. The design of this study uses a quasi experiment with a pre-test and post-test control group design approach. The study population is all chronic kidney failure patients undergoing routine hemodialysis at Prof. Dr. H. Aloei Saboe Hospital, totaling 60 patients. The sample was taken using the purposive sampling technique with 40 respondents who met the inclusion criteria, which were then divided into 20 intervention group respondents and 20 control group respondents. The fatigue level was measured using the Indonesian version of the FACIT-Fatigue scale instrument. Data analysis was conducted using an independent sample t-test. The results of the study found that the p-value = 0.000 (<0.05), so it can be concluded that there is a very significant difference in the effect on reducing fatigue levels between the intervention group that received intradialytic exercise and the control group that only received routine care. This is because intradialytic exercise can increase blood flow to the muscles which optimizes the cleansing of uremic toxin and increases energy metabolism, thereby effectively reducing the patient's fatigue level during hemodialysis.